Exploring the Molecular Mechanism of HongTeng Decoction against Inflammation based on Network Analysis and Experiments Validation - Yang, Yuanyuan; Bi, Chongwen; Li, Bin; Li, Yun; Song, Yin; Zhang, Minghui; Peng, Longxi; Fan, Dongmei; Duan, Rong; Li, Zhengxiang (Current Computer - Aided Drug Design, 2024)
Background: HongTeng Decoction (HTD) is a traditional Chinese medicine that is widely used to treat bacterial infections and chronic inflammation. However, its pharmacological mechanism is not clear. Here, network pharmacology and experimental verification were applied to investigate the drug targets and potential mechanisms of HTD in inflammation treatment. Methods: The active ingredients of HTD were collected from the multi-source databases and clarified by Q Exactive Orbitrap analysis in the treatment of inflammation. Then, molecular docking technology was used to explore the binding ability of key active ingredients and targets in HTD. In vitro experiments, the inflammatory factors and MAPK signaling pathways are detected to verify the anti-inflammatory effect of HTD on the RAW264.7 cells. Finally, the anti-inflammatory effect of HTD was evaluated in LPS induced mice model. Results: A total of 236 active compounds and 492 targets of HTD were obtained through database screening, and 954 potential targets of inflammation were identified. Finally, 164 possible targets of HTD acting on inflammation were obtained. The PPI analysis and KEGG enrichment analyses showed that the targets of HTD in inflammation were mostly related to the MAPK signaling pathway, the IL-17 signaling pathway, and the TNF signaling pathway. By integrating the results of the network analysis, the core targets of HTD in inflammation mainly include MAPK3, TNF, MMP9, IL6, EGFR, and NFKBIA. The molecular docking results indicated solid binding activity between MAPK3-naringenin and MAPK3-paeonol. It has been shown that HTD could inhibit the levels of inflammatory factors, IL6 and TNF-α, as well as the splenic index in the LPS-stimulated mice. Moreover, HTD could regulate protein expression levels of p-JNK1/2, and p-ERK1/2, which reflects the inhibitory effect of HTD on the MAPKS signaling pathway. Conclusion: Our study is expected to provide the pharmacological mechanisms by which HTD may be a promising anti-inflammatory drug for future clinical trials.
Keywords: inflammation